Public control and counteraction to corruption offences by means of social communications and networks - M. Kopotun, Igor (2020)
The research paper deals with identifying ways to strengthen the institutional capacity of citizens in the field of combating corruption and to create recommendations on measures to prevent corruption offenses. The genesis of criminologists' scientific opinion on the role of civil society institutions in the fight against corruption is analyzed. It is noted that scholars studied only fragments of the problem of public participation in the prevention of corruption offenses at different times. The study concerned only a general description of corruption offenses, their determination and ways of prevention, including, among others, the role played by NGOs in the anti-corruption process. When considering modern scientific research and international regulatory acts,